State of World Population 2018 - United Nations Population Fund (United Nations, 2018)
Human rights are universal, interrelated and interconnected. This publication highlights the fact that reproductive rights, one of the most fundamental rights inherent to all persons and one of the most intimate choices a person can make, are still not available to all. Evidence remains that the right to make choices remains limited for far too many women. The extent to which couples and individuals have the power to make their own decisions about whether and when to have children, and how many children to have, directly impacts fertility levels. Fertility levels vary greatly between developed countries and least developed countries. They provide a general indication of the state of reproductive rights. This publication shows that great disparities are often tied to social and economic inequities and need to be addressed.